Uses of Andersen health services utilization framework to determine healthcare utilization for mental health among migrants—a scoping review - Krzyż, Ewa Zuzanna; Antunez Martinez, Oscar Fidel; Lin, Hung-Ru (Frontiers in Public Health, 2023)
Migration is a worldwide occurrence that carries significant implications for healthcare systems, and it entails challenges to mental healthcare. Andersen Behavioral Model is widely used by the researchers to determine healthcare service utilization among many populations, including migrants. Our study aimed to explore the ways of using the Andersen Health System Utilization Framework in the literature to discover migrants’ mental healthcare utilization. This scoping review was based on Arksey and O’Malley’s framework. A comprehensive search was performed across five electronic databases. A total of 12 articles from January 1992 to July 2023 identified various versions of the Andersen Behavioral Model to provide an overview of mental health services utilization among migrants. The most used was the version from 1995, placing emphasis on individual characteristics and health behaviors rather than contextual characteristics and health outcomes. The analysis identified four significant trends in the literature. First, there is a predominant focus on individual characteristics over contextual factors. Second, researchers tend to integrate multiple versions of the Andersen Behavioral Model, and the most used was the version from 1995. Third, additional factors specific to migrant populations are incorporated into the model, but the categorization is sometimes unclear. Finally, the majority of studies used a quantitative approach and were based in North America, suggesting a focus on the significance of mental health in migrant communities in that context. The lack of a tailored framework specific to migrants and their mental healthcare utilization may be a contributing risk factor, therefore, findings from this review represent useful insights for organizations and policy administrators when formulating such services. Future research should consider health outcomes, such as consumer satisfaction as proposed by the Andersen Behavioral Model, along with contextual factors, as they are equally important in this issue. In summary, our scoping review calls for further research using the Andersen Behavioral Model to study mental healthcare utilization among migrants. Notable findings include the adaptation of the model to migrant populations, a focus on individual characteristics, a need for more diverse research methods, and the proposal of a new conceptual model to guide research and policy development.